Hakekat Manusia dan Dimensi-Dimensi Pendidikan Humanistik dalam Pandangan Islam - Kalsum, Ummi; Martedi, Ferry; Hilmin, Hilmin; Noviani, Dwi (STAI Denpasar Bali, 2024)
Humanization of education in an Islamic context, with emphasis on a deep understanding of human nature. Education that focuses on human nature in Islam views individuals as unique creatures who have value, potential and an important role in God's creation. This paper explains how Islam provides a philosophical and ethical basis for recognizing and respecting human dignity in the educational process.Next, review the dimensions of humanistic education that are in accordance with Islamic values. Humanistic education aims to develop humans holistically, including physical, mental, emotional and spiritual aspects. These dimensions include a curriculum approach that is oriented towards personal development, an inclusive educational environment, the teacher's role as a facilitator of growth, and learning that encourages understanding, reflection, and creativity.Through this presentation of human nature in Islam and the dimensions of humanistic education, it can provide in-depth insight into how education can be an important and significant medium in developing individuals who are dignified, empowered and ethical, in accordance with Islamic principles and values. humanity.